2016
DOI: 10.12944/cwe.11.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changing Climatic Conditions on Chill Units Accumulation and Productivity of Apple in Mid Hill Sub Humid Zone of Western Himalayas, India

Abstract: The present study was carried out during 2014-15 in the Kullu district of Himachal Pradesh, which is situated between 31º52’00” to 31º58’00” North latitude and 76º13’00” to 77º44’00” East longitudes.The cumulative chill units hours available for apple crop were calculated by using UTAH model for the period of 1986 to 2015 and a decrease of 6.38 chill units(CU) hours per year was recorded at Kullu Valley of Himachal Pradesh. Chill units for the last three decades i.e. 1986-1995, 1996-2005 and 2006-2015 also rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…The calculated chill units using station data trend in our results is in agreement with that of some other studies for apple cultivation in Himachal Pradesh. For example, Chand et al 2016 and Sen et al 2015 used the UTAH model to calculate the chill units of a station in Kullu district and found a similar decreasing trend as presented in the present study [ 37 , 38 ]. But, the use of Dale.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The calculated chill units using station data trend in our results is in agreement with that of some other studies for apple cultivation in Himachal Pradesh. For example, Chand et al 2016 and Sen et al 2015 used the UTAH model to calculate the chill units of a station in Kullu district and found a similar decreasing trend as presented in the present study [ 37 , 38 ]. But, the use of Dale.…”
Section: Discussionsupporting
confidence: 85%
“…and Sen et al 2015 used the UTAH model to calculate the chill units of a station in Kullu district and found a similar decreasing trend as presented in the present study [37,38]. But, the use of Dale.…”
Section: Plos Onesupporting
confidence: 83%
“…Thakur (1994) also supported that off-season vegetable production and marketing is the most profitable farm business giving very high production and income to farmers per unit area of land. The present findings are also in accordance with the findings of Sen et al (2015) and Chand et al (2016) who reported that there was a decreasing trend in the apple productivity of the order of (0.016 tonnes/ha/ year) during the period 1985-2009 in the Kullu valley due to non fulfillment of chill units.…”
Section: Reasons For Land Use Changessupporting
confidence: 93%
“…Among these, temperature and atmospheric CO 2 are the most highlighted climate elements for temperate tree crops. Extensive research in tree phenology has demonstrated that the increase in temperature and atmospheric CO 2 levels ultimately influences the number of chill hours required for dormancy breaking and the yield and fruit quality of temperate fruit crops [10,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (examples are given in Tables 1 and 2). Several studies have evaluated the productivity of temperate fruit crops with the current status of global climate change [4,33,[44][45][46][47][48][49][50][51][52][53].…”
Section: Climate Change and Temperate Fruit Productivitymentioning
confidence: 99%